Downregulation of the schizophrenia risk‐gene Dgcr2 alters early microcircuit development in the mouse medial prefrontal cortex. Issue 3 (11th March 2022) - Molinard‐Chenu, Aude; Godel, Michel; Rey, Alicia; Musardo, Stefano; Bodogan, Timea; Vutskits, Laszlo; Bellone, Camilla; Dayer, Alexandre
Abstract: Alterations in the generation, migration and integration of different subtypes of neurons in the medial prefrontal cortex (mPFC) microcircuit could play an important role in vulnerability to schizophrenia. Using in vivo cell‐type specific manipulation of pyramidal neurons (PNs) progenitors, we aim to investigate the role of the schizophrenia risk‐gene DiGeorge Critical Region 2 ( Dgcr2 ) on cortical circuit formation in the mPFC of developing mice. This report describes how Dgcr2 knock down in upper‐layer PNs impacts the functional maturation of PNs and interneurons (INs) in the mPFC. First, we demonstrate that Dgcr2 knock‐down disrupts laminar positioning, dendritic morphology and excitatory activity of upper‐layer PNs. Interestingly, inhibitory activity is also modified in Dgcr2 knock‐down PNs, suggesting a broader microcircuit alteration involving interneurons. Further analyses show that the histological maturation of parvalbumin (PV) INs is not dramatically impaired, thus implying that other INs subtypes might be at play in the reported microcircuit alteration. Overall, this study unravels how local functional deficits of the early postnatal development of the mPFC can be induced by Dgcr2 knock‐down in PNs. Abstract : Knock‐down of the schizophrenia risk‐gene Dgcr2 in pyramidal neurons of the medial prefrontal cortex in mice disrupts dendritogenesis and electrophysiological maturation of the local microcircuit.